2020
DOI: 10.1007/s00401-020-02224-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA methylation profiles in blood from patients with sporadic Creutzfeldt–Jakob disease

Abstract: Prion diseases are fatal and transmissible neurodegenerative disorders caused by the misfolding and aggregation of prion protein. Although recent studies have implicated epigenetic variation in common neurodegenerative disorders, no study has yet explored their role in human prion diseases. Here we profiled genome-wide blood DNA methylation in the most common human prion disease, sporadic Creutzfeldt–Jakob disease (sCJD). Our case–control study (n = 219), when accounting for differences in cell type compositio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Beyond ARSB and its association with MPS, we also noted 24 positional candidate genes related to 26 additional EMMAX GxE signals ( P -value ≤ 5E-05; Supplementary Table 2 , Fig. 1 ); the majority of which have previously been associated with Parkinson’s disease ( SMYD4 , WARS2 , IFNGR1 , PLPP4 , ASCL1 , FAM120A ), Alzheimer’s disease ( TBX15 , IFNGR , PTP4A1 , AIM2 , SLC10A2 , COL25A1 , ASCL1 , EPHB1 , UMAD1 , VNN3 , COL27A1 , RNF144B , SDK2 ), and various prion diseases ( IFNGR , SEC23IP , EPHA3 , EFNB2 , ELOVL4 , DOCK5 , COL27A1 ) including scrapie, bovine spongiform encephalopathy, and Creutzfeldt–Jakob disease ( Ide et al 2005 ; Julius 2008 ; Hashioka et al 2009 ; Tong et al 2010 ; Tian et al 2013 ; Woodling et al 2014 ; Majer 2015 ; Freeman and Ting 2016 ; Vélez et al 2016 ; Watson et al 2016 ; Mez et al 2017 ; Su et al 2018 ; Choubey 2019 ; Dabin 2019 ; Hirsch et al 2019 ; Liu et al 2019 ; Majer et al 2019 ; Meyer et al 2019 ; Thatra 2019 ; Bellenguez et al 2020 ; Dabin et al 2020 ; Donaldson et al 2020 ; Martinelli et al 2020 ; Wang et al 2020 ; Vastrad and Vastrad 2021 ). Notably, the EMMAX GxE mixed model solutions were also robust to the inclusion of additional fixed effect covariates (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond ARSB and its association with MPS, we also noted 24 positional candidate genes related to 26 additional EMMAX GxE signals ( P -value ≤ 5E-05; Supplementary Table 2 , Fig. 1 ); the majority of which have previously been associated with Parkinson’s disease ( SMYD4 , WARS2 , IFNGR1 , PLPP4 , ASCL1 , FAM120A ), Alzheimer’s disease ( TBX15 , IFNGR , PTP4A1 , AIM2 , SLC10A2 , COL25A1 , ASCL1 , EPHB1 , UMAD1 , VNN3 , COL27A1 , RNF144B , SDK2 ), and various prion diseases ( IFNGR , SEC23IP , EPHA3 , EFNB2 , ELOVL4 , DOCK5 , COL27A1 ) including scrapie, bovine spongiform encephalopathy, and Creutzfeldt–Jakob disease ( Ide et al 2005 ; Julius 2008 ; Hashioka et al 2009 ; Tong et al 2010 ; Tian et al 2013 ; Woodling et al 2014 ; Majer 2015 ; Freeman and Ting 2016 ; Vélez et al 2016 ; Watson et al 2016 ; Mez et al 2017 ; Su et al 2018 ; Choubey 2019 ; Dabin 2019 ; Hirsch et al 2019 ; Liu et al 2019 ; Majer et al 2019 ; Meyer et al 2019 ; Thatra 2019 ; Bellenguez et al 2020 ; Dabin et al 2020 ; Donaldson et al 2020 ; Martinelli et al 2020 ; Wang et al 2020 ; Vastrad and Vastrad 2021 ). Notably, the EMMAX GxE mixed model solutions were also robust to the inclusion of additional fixed effect covariates (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, and in contrast to AD ( 38 ), PD ( 41 ), and ALS ( 42 ), only one study has analyzed the genome-wide methylation profile in prion diseases, and this was performed in peripheral blood of sCJD patients ( 23 ). We report here the first WGBS study carried out in the CNS of any prion disease model.…”
Section: Discussionmentioning
confidence: 99%
“…However, methylation has not been observed in the promoter of the rat PRNP gene, at least in PC12 cells ( 22 ). Regarding prion diseases, DNA methylation studies at a genomic level have only been performed in blood from patients with sporadic Creutzfeldt–Jakob disease (sCJD), the most common human prion disease ( 23 ). To the best of our knowledge, no genome-wide DNA methylation studies have yet been reported in the CNS of any prion disease models or naturally infected cases.…”
Section: Introductionmentioning
confidence: 99%
“…Final DNA samples were stored at 4 °C until needed. DNA extraction from CJD brain samples was carried out in a Biosafety Level 3 facility as previously published 49 .…”
Section: Methodsmentioning
confidence: 99%